Problematizing the presentation and reception of political brands: The strategic and operational nature of the political Brand alignment model. (18th November 2019) - Pich, Christopher; Armannsdottir, Guja; Dean, Dianne; Spry, Louise; Jain, Varsha
Abstract : Purpose: There are explicit calls for research devoted to how political actors present their brand to the electorate and how this is interpreted. Responding to this, the purpose of this paper is to build an understanding of how political brand messages and values are received and aligned with voter expectations, which in turn shapes the consistency of a political brand. Design/methodology/approach: Using an interpretivist perspective, this two-stage approach first focuses on semi-structured interviews with internal stakeholders of the UK Conservative Party and second uses focus group discussions with external stakeholders (voters) of age 18-24 years. Data was collected between 1 December 2014 and 6 May 2015. Findings: The findings suggest that the UK Conservative brand had recovered from the "nasty party" reputation. Further, the Conservative brand was perceived as credible, trustworthy and responsible, with positive associations of "economic competence". However, while the nasty party imagery has declined, the UK Conservative brand continues to face challenges particularly in terms of longstanding negative associations perceived by both internal and external markets. Research limitations/implications: It must be acknowledged that all research methods have their own limitations, and acknowledging these will strengthen the ability to draw conclusions. In this study, for example, due to time constraints during the election campaign period, 7 participants supported stage one of the study and 25 participants supported stage two of the study. However, participants from stage one of the study represented all three elements of the UK Conservative Party (Parliamentary, Professional and Voluntary). In addition, the elite interviews were longer in duration and this provided a greater opportunity to capture detailed stories of their life experiences and how this affected their brand relationship. Similarly, participants for stage two focussed on young voters of age 18-24 years, a segment actively targeted by the UK Conservative Party. Practical implications: The brand alignment framework can help practitioners illuminate components of the political brand and how it is interpreted by the electorate. The increasing polarisation in politics has made this a vital area for study, as we see need to understand if, how or why citizens are persuaded by a more polarised brand message. There are also social media issues for the political brand which can distort the carefully constructed brand. There are opportunities to evaluate and operationalize this framework in other political contexts. Originality/value: The brand alignment model extends current branding theory first by building on an understanding of the complexities of creating brand meaning, second, by operationalizing differences between the brand and how it is interpreted by the electorate, finally, by identifying if internal divisions within the political party pose a threat to the consistency of the brand.